2016
DOI: 10.1080/13621718.2015.1124504
|View full text |Cite
|
Sign up to set email alerts
|

A phase field investigation of dendrite morphology and solute distributions under transient conditions in an Al–Cu welding molten pool

Abstract: A quantitative phase field model is developed to simulate dendrite morphology and solute distributions of the Al-4 wt-% Cu alloy in Gas Tungsten Arc Welding (GTAW) welding molten pool under transient conditions. The functions of temperature gradient and travel velocity are used to obtain transient conditions of the welding molten pool. Time evolutions of the dendrite morphology, solute distributions of different positions and interfaces are obtained. The dendrite growth process can be divided into four stages,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In the past decades, phase-field modeling has been widely used for the simulation of microstructure evolution in the solidification process [13] and for high-speed processes as RP-welding [14,15]. The progress of the phase evolution is dependent to minimizing the free energy functional.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, phase-field modeling has been widely used for the simulation of microstructure evolution in the solidification process [13] and for high-speed processes as RP-welding [14,15]. The progress of the phase evolution is dependent to minimizing the free energy functional.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al studied the microstructure evolution during solidification of welding molten pool. They found that the columnar dendrite growth during welding can be divided into four stages: linear growth stage, nonlinear growth stage, competitive growth stage and relatively steady growth stage [22]. In our early stage works, the variation of maximum undercooling ahead of planar S/L interface with time at linear growth stage is shown in Figure 3.…”
Section: Computational Detailsmentioning
confidence: 73%
“…The radius of heterogeneous nuclei was 2 ∆x. [22]. In our early stage works, the variation of maximum undercooling ahead of planar S/L interface with time at linear growth stage is shown in Figure 3.…”
Section: Computational Detailsmentioning
confidence: 95%
“…The increase trend is more obvious with the decrease of the welding velocity. In the study conducted by Wang et al, 30 the evolution of the dendrite in the welding molten pool is divided into the linear growth period, the nonlinear growth period, the competitive growth period and the short-term steady growth period. In this work, the primary dendrite arm spacing at the short-term steady growth period is investigated and discussed.…”
Section: Primary Dendrite Arm Spacing Under Different Welding Velocitiesmentioning
confidence: 99%